2012
DOI: 10.1007/s00535-012-0693-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk of peritoneal carcinomatosis by endoscopic ultrasound-guided fine needle aspiration for pancreatic cancer

Abstract: EUS-FNA for pancreatic cancer did not significantly increase the risk of peritoneal carcinomatosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 12 publications
7
35
0
Order By: Relevance
“…A multivariate analysis did not find a significant correlation between preoperative EUS-FNA and cancer recurrence in the stomach or peritoneal cavity [7] . Similar results were obtained in 2 other retrospective studies in which EUS-FNA did not increase the risk of tumor dissemination through the needle tract in pancreatic cancer [10,11] . Regarding mucinous pancreatic cystic lesions, the PIPE study was conducted to assess the frequency of postoperative peritoneal seeding in patients with intraductal papillary mucinous neoplasm.…”
Section: Risk Of Needle Tract Seeding Following Eus-fnasupporting
confidence: 79%
“…A multivariate analysis did not find a significant correlation between preoperative EUS-FNA and cancer recurrence in the stomach or peritoneal cavity [7] . Similar results were obtained in 2 other retrospective studies in which EUS-FNA did not increase the risk of tumor dissemination through the needle tract in pancreatic cancer [10,11] . Regarding mucinous pancreatic cystic lesions, the PIPE study was conducted to assess the frequency of postoperative peritoneal seeding in patients with intraductal papillary mucinous neoplasm.…”
Section: Risk Of Needle Tract Seeding Following Eus-fnasupporting
confidence: 79%
“…Because a majority of patients included in this study had benign intraductal papillary mucinous neoplasm, the results could not be applicable to patients with malignant solid tumours. A study by Ikezawa et al 17 reported that patients with pancreatic adenocarcinoma who had undergone EUS-FNA (n=56) did not significantly increase the risk of peritoneal carcinomatosis. The impact of EUS-FNA on survival was not reported in this study.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, EUS‐FNA has been noted to have a lower morbidity and mortality compared with surgical diagnostic techniques. It has also been reported that needle tract seeding is markedly reduced when using EUS‐FNA compared with core needle biopsy and image‐guided percutaneous FNA . Clinical guidelines describing indications and techniques of EUS‐FNA as well as the terminology and nomenclature of pancreatobiliary disease, ancillary tests, and post‐FNA management have become available …”
Section: Introductionmentioning
confidence: 99%